Nanocarrier-Mediated Delivery of miRNA, RNAi, and CRISPR-Cas for Plant Protection: Current Trends and Future Directions - Mujtaba, Muhammad; Wang, Depeng; Carvalho, Lucas Bragança [UNESP]; Oliveira, Jhones Luiz [UNESP]; Espirito Santo Pereira, Anderson Do [UNESP]; Sharif, Rahat; Jogaiah, Sudisha; Paidi, Murali Krishna; Wang, Lichen; Ali, Qasid; Fraceto, Leonardo Fernandes [UNESP] (American Chemical Society (ACS), 2021)
Current trends in plant genetic transformation technologies, i.e., designing and applying molecules like miRNA, RNAi, and CRISPR-Cas, largely enable researchers to target specific sites in the plant genome to avert the growing biotic and abiotic threats to plants. However, the delivery of these molecules through conventional techniques brings an array of drawbacks such as low efficiency due to the cell wall barrier, tissue damage that leads to browning or necrosis, degradation of these biomolecules by physiological conditions (high temperature, harsh pH, and light), and plant-specific protocols. The advancements in nanotechnology offer an excellent alternative for the safe and highly efficient delivery of biomolecules such as miRNA, CRISPR-Cas, and RNAi without damaging the plant tissues. Nanoparticle (polymeric, metallic, magnetic, silica, carbon, etc.)-based delivery of biomolecules can be efficiently utilized especially for plant protection applications. Herein, we present a comprehensive overview of current trends (with a focus on the previous five years) in nanoparticle-based delivery of miRNA, RNAi, CRISPR-Cas and simillar biomolecules for plant protection applications. In addition, a future perspective focuses on the research gaps and unexplored potentials of nanoparticles for the delivery of biomolecules.
Keywords: chitosan; controlled delivery; DNA origami; nanoparticles; plant protection; silica